Scalable synthesis of BiVO4 thin films via anodic plating and thermal calcination - Jiang, Haoyang; Xiao, Yongcheng; Zhong, Miao (Discover nano, 2023)
Fabrication of high-quality semiconductor thin films has long been a subject of keen interest in the photocatalytic field. Here, we report a facile, solution-based anodic plating and calcination for large-scale synthesis of BiVO 4 thin films on indium tin oxide coated glass for use as photoanodes in solar water splitting. Using Na 2 SO 3 as a sacrificial reagent, continuous solar H 2 production with 94% Faradaic efficiency was obtained over 6 h of photoelectrochemical water splitting.